Hydrothermal synthesis and crystal structure of a copper(ii) coordination polymer with bridging dicarboxylate and diamine ligands - Legendre, Alexandre de O. [UNESP]; Mauro, Antonio Eduardo [UNESP]; Nogueira, Vânia Martins [UNESP]; Castellano, Eduardo E. (My University, 2008)
This work reports on the synthesis of a copper(II) coordination compound with 4,4-oxibis(benzoate) (obb) and trans-1,2- bis(4-pyridyl)ethene (bpe) ligands. The complex was characterized by single-crystal X-ray diffraction, which showed a 3D polymeric structure. Each copper center is surrounded by four oxygen atoms at the basal plane and one nitrogen atom and one copper atom at the axial positions, revealing a distorted octahedral geometry. Four carboxylic groups bridge two copper atoms, forming a cage-like structure, with the distance between the metallic centers being 2.656(1)Å. 2008 © The Japan Society for Analytical Chemistry.